Factors contributing to fourth graders’ mathematics achievement: a multilevel study - Rasmuin, Rasmuin; Retnawati, Heri; Kartianom, Kartianom; Kassymova, Gulzhaina K. (Institute of Advanced Engineering and Science, 2024)
This study aims to determine the factors that influence the mathematics achievement of grade 4 students in Indonesia at the student and school level using Trends in International Mathematics and Science Study (TIMSS) 2015 data. Sample in this study were all grade 4 students in Indonesia who participated in TIMSS 2015. There are 4,025 students from 230 schools. The TIMSS 2015 data used in this study was analyzed using a multilevel model (MLM) using the R package ‘lme4’ software. The results of this study indicate that i) the school visited by each student accounts for the majority of the variance in the mathematics achievement of Indonesian grade 4 students (51%); ii) factors related to students’ self-construction of mathematics such as attitude-toward mathematics (ATM) and self-concept and factors related to schools such as socioeconomic status (SES) school, self-concept school, school readiness, general school resources, and teacher education level was found to influence students’ mathematics achievement positively and significantly, where self-concept school was the strongest predictor compared to other predictors; and iii) variables at the student and school level explain 35% of the total variance in Indonesian grade 4 students’ mathematics achievement.